AN ANALYSIS OF SADISTIC IN ERAGON NOVEL - Diana, Eli; Astuti, Rina (LITERARY CRITICISM, 2014)
Psychoanalysis is one of subject in literature about psychology because it plays the imagination and situation around the author such as reality, fantasies and dreams. There are many aspects that can be investigated in psychoanalysis, such as narcissism, idealism, heroism and sadism. In this study the writer find out about types of sadist and the dominant types that are in Eragon novel by using Theodore Millon theory. The result of this study are eleven types of sadists on Galbatorixâs character in Eragon Novel. It divided into two explosive sadists, four tyrannical sadists, two enforcing sadists, and three spineless sadists. From that data brutalize, relish menacing, and cruel in verbal act of Galbatorix did to people and Rider clan is indicate tyrannical sadist which be the dominant types that are in Eragon novel. He enjoys fearless of people by killed and relish menacing them.Â Keywords : Sadist, Eragon novel.